Effects of Sensorimotor Synchronization Training on Anticipatory Postural Adjustments according to the Muscle Function in the Elderly - Eunhwi Jeong; Donghwi Suh; Jaeuk Jeong (Asian Society of Kinesiology, 2023)
OBJECTIVES Anticipatory postural adjustments (APA) are used by humans to counteract the perturbation caused by the initiation of walking. Many previous studies have shown that APA can be improved through sensorimotor interventions. Therefore, the purpose of this study is to investigate the effectiveness of sensorimotor intervention strategies for improving APA in the elderly. METHODS 20 healthy elderly participants were recruited and divided into two groups according to the diagnostic criteria for sarcopenia. Sensorimotor synchronization training (SMSt) utilizing auditory signals was used as intervention to improve the APA. APA was measured during the performance of lifting the foot and narrow walking tasks to compare the continuity of movement, and walking speed was measured to assess task performance. In order to compare the change of APA, we compared the displacement of center of pressure (COP) and torque before the movement occurred. RESULTS The results showed that the inter limb transfer effect was observed in all tasks. Although no difference between the group was observed in the foot raising task, there were significant increase in the foot speed, the magnitude and torque of the APA. Such changes are considered as a strategy for offsetting an increased perturbation of the faster foot after SMSt. Unlike the raising foot task, different aspects were observed in the narrow stride walking task. In the narrow stride walking task, although the foot speed increased, there was no increase in the magnitude and torque of APA. Furthermore, the group with low muscle function showed a decrease in static. CONCLUSIONS The differences in the continuity of motor tasks observed in this study support the hypothesis that SMSt can enhance motor control and improve postural function.